2010
DOI: 10.1002/zaac.201000154
|View full text |Cite
|
Sign up to set email alerts
|

The Layered Coordination Polymer Bi(SCN)3·1/2H2O

Abstract: All thiocyanate anions bind with both ends to different cations. The coordination network expands in plane layers parallel (1 1 0). The water molecule coordinates one of the two independent Bi 3+ cations. Dehydration sets in at 100 °C, followed by stepwise thermal decomposition to Bi 2 S 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
(25 reference statements)
4
14
0
Order By: Relevance
“…The vibrational frequencies obtained from the ATR‐FT infrared and the single‐crystal Raman spectra of [Yb(NCS) 3 (H 2 O) 5 ] · H 2 O (Figure ) compare well to the frequencies for the free (SCN) – anion, [Dy(NCS) 3 (H 2 O) 5 ] · H 2 O and the related bismuth(III) thiocyanate hemihydrate Bi(NCS) 3 · 1 / 2 H 2 O (Table ). However, in the range from 990 to 1200 cm –1 in the ATR‐FTIR spectrum vibrational modes of Ba(SO 4 ) impurities seem to be present…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The vibrational frequencies obtained from the ATR‐FT infrared and the single‐crystal Raman spectra of [Yb(NCS) 3 (H 2 O) 5 ] · H 2 O (Figure ) compare well to the frequencies for the free (SCN) – anion, [Dy(NCS) 3 (H 2 O) 5 ] · H 2 O and the related bismuth(III) thiocyanate hemihydrate Bi(NCS) 3 · 1 / 2 H 2 O (Table ). However, in the range from 990 to 1200 cm –1 in the ATR‐FTIR spectrum vibrational modes of Ba(SO 4 ) impurities seem to be present…”
Section: Resultssupporting
confidence: 52%
“…The ATR‐FT infrared spectrum was obtained by introducing powdered material of the title compound in a nitrogen‐filled glove box into the beam of a Nicolet iS5‐FTIR spectrometer (Thermo Fisher Scientific, Waltham, MA, USA) equipped with an attenuated total reflection unit. The combined vibrational spectra of [Yb(NCS) 3 (H 2 O) 5 ] · H 2 O are displayed in Figure , whereas Table contains the exact frequencies and their assigned modes compared to data of the free thiocyanate anion in aqueous solution, [Dy(NCS) 3 (H 2 O) 5 ] · H 2 O and Bi(NCS) 3 · 1 / 2 H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of H 3 [Bi(SCN) 6 ] was adapted from ref. 20. Bi 2 O 2 (CO 3 ) (0.50 g, 0.98 mmol) was suspended in ca.…”
Section: Synthesis Of H 3 [Bi(scn) 6 ] Solution and Bi(scn)mentioning
confidence: 99%
“…Previous work has established that the homoleptic octahedral [Bi(SCN) 6 ] 3À anion can be used to form framework structures, in the alkali metal double hexagonal perovskite Cs 2 Na[Bi(SCN) 6 ] and the nickel arsenide structured Ln[Bi(SCN) 6 14,16 In addition, [Bi(SCN) 3 ] 3À has been reported to form an insoluble compound suitable for a quantitative chemical analysis with chromium(III) solutions. 19 A further interesting feature of these bismuth thiocyanate frameworks are their yellow and orange colours, also found in bismuth thiocyanate hemihydrate 20 There are, however, no reported structures or physical properties of either cubic perovskite derived structures or transition metal based bismuth thiocyanate frameworks. In this paper we report the synthesis, structure and optical properties of three analogues of the cyanide Prussian blues, the thiocyanate frameworks M III [Bi(SCN) 6 ]; M ¼ Fe, Cr and Sc, each of which is strongly coloured.…”
mentioning
confidence: 99%
“…Additionally, poly meric bismuth alkoxides (Whitmire et al, 1992;Roggan et al, 2005;Kricheldorf et al, 2008;Breunig et al, 2009b) have been reported as well as coordination polymers with sulfur-or seleniumcontaining donor ligands (Barton et al, 2000;Yim et al, 2000;Briand et al, 2012). Bismuth halides and pseudo halides are also capable of forming coordination polymers (Clegg et al, 1992(Clegg et al, , 1993Wang et al, 1997;Breunig et al, 2009a;Erbe et al, 2010;Koch and Ruck, 2010), and additionally, aromatic π donors (Silvestru et al, 1999;Mehring and Schürmann, 2001;Schmidbaur and Schier, 2008;Auer et al, 2009;Caracelli et al, 2013), organometallic ligands (Roggan et al, 2005), hexacyanoferrates (Perera et al, 2011), and polyoxometallates (Xu et al, 2007) were shown to bridge bismuth atoms to give unusual coordination polymers.…”
Section: Introductionmentioning
confidence: 95%